Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1621
|View full text |Cite
|
Sign up to set email alerts
|

Approaching Human Performance in Behavior Estimation in Couples Therapy Using Deep Sentence Embeddings

Abstract: Identifying complex behavior in human interactions for observational studies often involves the tedious process of transcribing and annotating large amounts of data. While there is significant work towards accurate transcription in Automatic Speech Recognition, automatic Natural Language Understanding of high-level human behaviors from the transcribed text is still at an early stage of development. In this paper we present a novel approach for modeling human behavior using sentence embeddings and propose an au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Finally, we applied a neural network on top of the embeddings to estimate actual behavior ratings. For this section we applied the framework proposed in [12]. Sessions were segmented into sentences and represented as a sequence of embeddings.…”
Section: Rating Estimation Using Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we applied a neural network on top of the embeddings to estimate actual behavior ratings. For this section we applied the framework proposed in [12]. Sessions were segmented into sentences and represented as a sequence of embeddings.…”
Section: Rating Estimation Using Neural Networkmentioning
confidence: 99%
“…The final session label was obtained by training a Support Vector Regressor to map from the median of the window predictions to the session rating. For more details the reader can refer to [12].…”
Section: Rating Estimation Using Neural Networkmentioning
confidence: 99%
“…More details about the recruitment, data collection and the annotations can be found in (Christensen et al, 2004;Baucom et al, 2011). Consistent with previous work (Lee et al, 2010;Georgiou et al, 2011;Black et al, 2013;Lee et al, 2014;Tseng et al, 2017), for each participant and behavior, we take the average of the annotators' ratings as the true rating in that session. Therefore, each speaker's data sample consists of the manual transcription of their utterances and their behavior ratings in that session.…”
Section: Description Of Corpusmentioning
confidence: 99%
“…Subsequently, there have been efforts (Narayanan and Georgiou, 2013) to automate this behavior annotation (or coding) process using machine learning so that rapid and inexpensive feedback can be provided to the stakeholders. Previous work has shown that automated coding systems are effective at quantifying behaviors from speech and spoken language such as Negativity (Georgiou et al, 2011;Black et al, 2013;Chakravarthula et al, 2015a;Tseng et al, 2017), Depression (Gupta et al, 2014;Morales et al, 2018) and Empathy (Xiao et al, 2012;Gibson et al, 2016;Pérez-Rosas et al, 2017). However, there are some critical aspects of this behavior assessment process which humans can handle naturally and easily but machines still cannot, one of which is the notion of how much to observe in order to reliably assess behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation